2023
DOI: 10.3390/ijerph20032093
|View full text |Cite
|
Sign up to set email alerts
|

The Consequences of the COVID-19 Pandemic on Emergency Surgery for Colorectal Cancer

Abstract: The aim of this study is to analyze the impact of the COVID-19 pandemic on the emergency treatment of patients with colorectal cancer in a university surgery clinic. Data from patients undergoing emergency surgery during the pandemic period (2020–2021) was taken into consideration and the results were analyzed and compared with the periods 2016–2017 and 2018–2019. A significant decrease in the number of patients undergoing emergency surgery was reported (p = 0.028). The proportion of patients who presented mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Most of the included articles were from high-income countries (HICs) (i.e., n = 38, 76.0% from HICs and n = 12, 24.0% from low- and middle-income countries [LMICs]). Seventeen studies reported on the ‘impact of COVID-19’ [ 25 , 27 , 44 , 47 , 48 , 50 52 , 57 , 68 – 73 , 75 ], 30 reported on ‘health system responses, effects or challenges’ [ 6 , 7 , 18 , 21 24 , 38 , 40 43 , 45 , 46 , 49 , 53 56 , 58 67 , 74 ] and 3 reported on both [ 5 , 26 , 39 ]. We present the key findings below in a narrative synthesis, according to the primary outcomes ( S1 Checklist ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the included articles were from high-income countries (HICs) (i.e., n = 38, 76.0% from HICs and n = 12, 24.0% from low- and middle-income countries [LMICs]). Seventeen studies reported on the ‘impact of COVID-19’ [ 25 , 27 , 44 , 47 , 48 , 50 52 , 57 , 68 – 73 , 75 ], 30 reported on ‘health system responses, effects or challenges’ [ 6 , 7 , 18 , 21 24 , 38 , 40 43 , 45 , 46 , 49 , 53 56 , 58 67 , 74 ] and 3 reported on both [ 5 , 26 , 39 ]. We present the key findings below in a narrative synthesis, according to the primary outcomes ( S1 Checklist ).…”
Section: Resultsmentioning
confidence: 99%
“…Five case-series studies, conducted at an institutional level, compared the number of colorectal cancer procedures performed during the pandemic to that performed during preceding years, pre-COVID-19; one of the studies was from an UMIC (China) and four were from HICs (Italy, Romania, Croatia) [ 39 , 57 , 68 , 70 , 75 ]. The relative percentage reduction in the institutional volume of elective colorectal procedures performed ranged from 11.08%–57.3% across these studies [ 39 , 57 , 68 , 70 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 pandemic required a series of measures from public and private healthcare systems to address the increasing number of infections. These healthcare systems focused mainly on the management of patients infected with the SARS-CoV-2 virus, and as a result, oncological diseases were neglected during the pandemic period 15 .…”
Section: Discussionmentioning
confidence: 99%
“…CRC management was severely impacted by the pandemic 15 . The screening strategies for this disease were seriously reduced during the pandemic period, with many patients remaining undiagnosed 11 .…”
Section: Introductionmentioning
confidence: 99%